Reply to the comment on: “Dalbavancin for infective endocarditis: a systematic review of effectiveness, safety, and dosing” - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Dalbavancin for infective endocarditis: A systematic review of effectiveness, safety, and dosing - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Infective endocarditis (IE) requires prolonged intravenous antibiotic therapy, leading to extended hospitalization and increased morbidity. Dalbavancin, a long-acting antibiotic with excellent tissue penetration and a favorable safety profile, can be a promising alternative. This systematic review aimed to investigate the current literature regarding the use of dalbavancin for infective endocarditis. Methods A systematic search of PubMed and Scopus was conducted according to PRISMA guidelines. Eligible studies included adult patients (≥ 18 years) with IE diagnosed by the modified Duke criteria, treated with dalbavancin as monotherapy or sequential/consolidation therapy. Data extraction included demographics, type of IE, causative pathogen, dosing regimen, surgical intervention, adverse events, and outcomes. Descriptive analyses were performed. Results Thirty-eight studies including 565 patients were analyzed. The overall cure rate was 88.0%, with a similar success rate across native valve (90.1%), prosthetic valve (90.0%), and cardiac device-related IE (86.0%). Staphylococcus aureus , Coagulase-negative staphylococci (CNS), Streptococcus spp ., and Enterococcus faecalis were the most common pathogens. Cure rates were comparable among most pathogens, though a lower cure rate was evident in infections due to Enterococcus faecalis compared to Streptococcus spp. (80.7% vs. 96.6%, p = 0.008). An effective antimicrobial exposure of 2 weeks had similar success rate compared to a longer period of effective antimicrobial exposure ( p = 0.31). Adverse events were rare (2.9%), with mild rash being the most common. Conclusions Dalbavancin demonstrates high cure rates and excellent tolerability in IE, and could offer an attractive alternative to conventional prolonged intravenous therapy. Further randomized controlled trials are warranted to define standardized protocols.

Enhancement of muscle activation during squat exercise: evaluation with magnetic resonance imaging - Riccardo G. Sorrentino; Andrej Vovk; Dušan Šuput; Leonidas G. Ioannou; Veronika Mekjavic; Rodrigo Fernandez-Gonzalo; Matej Supej; Igor B. Mekjavic (European Journal of Applied Physiology, 2025)
We evaluated whether vibration augmented muscle use during squat exercise with magnetic resonance imaging, with two methods: spin–spin relaxation time (T2 mapping), and volume analysis. Male participants ( n = 13) visited the facility on two occasions. During the first visit, each participant completed a resistance exercise (RE) comprising four sets of 12 repetitions of triple extension squats. Before and immediately after completion of the exercise, magnetic resonance imaging of their thigh and calf muscles was performed. During the second visit, participants performed resistance vibration exercise (RVE) using the same protocol, but standing on a vibration plate that provided a whole-body vibration stimulus (20 Hz, 3.5 mm amplitude) during the exercise. RE promoted increased T2 in vastus lateralis , vastus medialis and vastus intermedius muscles ( p < 0.0001). The same activation was observed for RVE, with no differences compared to RE. The volumetric method was less effective in assessing muscle activation. Only the vastus medialis and vastus intermedius muscle volumes were significantly greater post-exercise compared to pre-exercise for both RE (both muscles: p = 0.0009) and RVE (respectively: p = 0.005 and p = 0.009). No muscular activation was detected for calf either with T2 or volumetric method. Resistance exercise increased T2 and volume of some muscles of the thigh. The addition of whole-body vibration to resistance exercise does not enhance T2 relaxation time or volume accumulation.

Ultrahigh surface area nanoporous carbon for air and water purification: Pushing the boundaries and unveiling the key physicochemical features - Dimitrios A. Giannakoudakis; Ioannis Ioannidis; Kyriacos Ioannou; Eleni D. Salonikidou; Fivos Florides; Stefan Zeiler; Nikolaos Kostoglou; Mariusz Barczak; Konstantinos Triantafyllidis; Ioannis Pashalidis; Claus G. Rebholz (Chemical Engineering Journal, 2025)

Active interactions between animals and technology: biohybrid approaches for animal behaviour research - M. Papadopoulou; M. Ball; P. Bartashevich; A.L.J. Burns; V. Chiara; M.A. Clark; B.R. Costelloe; M. Fele; F. French; S. Hauert; M.K. Heinrich; J.E. Herbert-Read; et al. (Animal Behaviour, 2025)

Effects of 24-h sleep deprivation on whole-body heat exchange in young men during exercise in the heat - Nicholas J. Koetje; Nathalie V. Kirby; Fergus K. O’Connor; Brodie J. Richards; Kristina-Marie T. Janetos; Leonidas G. Ioannou; Glen P. Kenny (European Journal of Applied Physiology, 2025)

eDNA metabarcoding of marine invertebrate communities at RO desalination plant outfalls in Cyprus - K. Grammatiki; N. de Jonge; J.L. Nielsen; S.C. García-Gomez; E. Avramidi; M.M. Lymperaki; M. Marcou; G. Ioannou; M. Papatheodoulou; O. Dargent; D. Xevgenos; M. Hesselsøe; et al. (Marine Pollution Bulletin, 2025)

Effect of fluid temperature on the relation and agreement between perceptual and physiological strain during simulated work in a hot environment - Fergus K. O'Connor; Brodie J. Richards; Leonidas G. Ioannou; Glen P. Kenny (Journal of Thermal Biology, 2025)

Validation of Core, Rectal and Skin Temperature Predictions of a Free Web-Based Predictive Heat Strain Software Based on the ISO 7933:2023 Standard in Recreational Athletes - Konstantinos Mantzios; Leonidas G. Ioannou; Eftihia Nikolaki; Paraskevi Gkiata; Georgia Charachousou; Lydia Tsoutsoubi; Petros C. Dinas; Andreas D. Flouris (Journal of Science in Sport and Exercise, 2024)

No association between markers of systemic inflammation and endothelial dysfunction with Alzheimer’s disease progression: a longitudinal study - Arne van Setten; Jeroen F. Uleman; René J. F. Melis; Brian Lawlor; Niels P. Riksen; Jurgen A. H. R. Claassen; Rianne A. A. de Heus; Ricardo Segurado; Sean Kennelly; Marcel G. M. Olde Rikkert; Robert Howard; Florence Pasquier; et al. (GeroScience, 2024)
Introduction Systemic inflammation and endothelial dysfunction are potentially modifiable factors implicated in Alzheimer’s disease (AD), which offer potential therapeutic targets to slow disease progression. Methods We investigated the relationship between baseline circulating levels of inflammatory (TNF-α, IL-1ß) and endothelial cell markers (VCAM-1, ICAM-1, E-selectin) and 18-month cognitive decline (ADAS-cog12) in 266 mild-to-moderate AD patients from the NILVAD study. We employed individual growth models to examine associations, potential mediation, and interaction effects while adjusting for confounders. Results The average increase in ADAS-cog12 scores over all patients was 8.1 points in 18 months. No significant association was found between the markers and the rate of cognitive decline. Mediation analysis revealed no mediating role for endothelial cell markers, and interaction effects were not observed. Discussion Our results do not support the role of systemic inflammation or endothelial dysfunction in progression in persons with AD.

Central versus peripheral mechanisms of cold-induced vasodilation: a study in the fingers and toes of people with paraplegia - Lydia Tsoutsoubi; Leonidas G. Ioannou; Billie K. Alba; Stephen S. Cheung; Hein A. Daanen; Igor B. Mekjavic; Andreas D. Flouris (European Journal of Applied Physiology, 2023)
Purpose This study examined physiological and perceptual parameters related to cold-induced vasodilation (CIVD) in the fingers and toes of people with paraplegia and compared them with responses observed in able-bodied individuals. Methods Seven participants with paraplegia and seven able-bodied individuals participated in a randomized matched-controlled study involving left-hand and -foot immersion in cold water (8 ± 1 °C) for 40 min during exposure to cool (16 ± 1 °C), thermoneutral (23 ± 1 °C), and hot (34 ± 1 °C) ambient conditions. Results Similar CIVD occurrence was observed in the fingers in the two groups. In toes, three of the seven participants with paraplegia revealed CIVDs: one in cool, two in thermoneutral, and three in hot conditions. No able-bodied participants revealed CIVDs in cool and thermoneutral conditions, while four revealed CIVDs in hot conditions. The toe CIVDs of paraplegic participants were counterintuitive in several respects: they were more frequent in cool and thermoneutral conditions (compared to the able-bodied participants), emerged in these conditions despite lower core and skin temperatures of these participants, and were evident only in cases of thoracic level lesions (instead of lesions at lower spinal levels). Conclusion Our findings demonstrated considerable inter-individual variability in CIVD responses in both the paraplegic and able-bodied groups. While we observed vasodilatory responses in the toes of participants with paraplegia that technically fulfilled the criteria for CIVD, it is unlikely that they reflect the CIVD phenomenon observed in able-bodied individuals. Taken together, our findings favor the contribution of central over peripheral factors in relation to the origin and/or control of CIVD.

Efficacy of cooling vests based on different heat-extraction concepts: The HEAT-SHIELD project - Urša Ciuha; Tamara Valenčič; Leonidas G. Ioannou; Igor B. Mekjavic (Journal of Thermal Biology, 2023)

Residual efficacy of selected larvicides against Culex pipiens pipiens (Diptera: Culicidae) under laboratory and semi-field conditions - Maria K. Sakka; Charalampos S. Ioannou; Nikos T. Papadopoulos; Christos G. Athanassiou (Environmental Science and Pollution Research, 2023)
Mosquitoes are a threat worldwide since they are vectors of important pathogens and parasites such as malaria, dengue, yellow fever, and West Nile. The residual toxicity of several commercial mosquito larvicides was evaluated for the control of Culex pipiens pipiens under controlled laboratory and semi-field conditions during late spring and summer of 2013. The evaluation included six different active ingredient formulations, i.e., diflubenzuron Du-Dim), Bacillus thuringiensis var. israelensis ( Bti ) (Vectobac), spinosad (Mozkill), S-methoprene (Biopren), temephos (Abate), and polydimethylsiloxane (PDMS) (Aquatain), that are currently registered of and had been registered in the past for mosquito control. Under controlled laboratory conditions, the residual activity ranged from 1 week (S-methoprene) up to 2 months (spinosad, PDMS). Exposure of larvicides under semi-field conditions resulted in noticeable differences regarding their efficacy as compared to the laboratory bioassays. Exposure of S-methoprene, Bti , and spinosad, for up to 3 days, resulted in similar adult emergence to the controls. On the other hand, the residual efficacy of diflubenzuron, temephos, and PDMS ranged from 14 to 28 days, depending on the season of exposure. Longevity and fecundity of adults that had emerged from surviving larvae, in most of the cases tested, did not differ significantly from that of the controls. The results of the present study demonstrate the necessity of both field and laboratory studies to draw safe conclusions regarding the efficacy of larvicides against mosquitoes and the selection of the proper formulation for each application scenario. In addition, defining the seasonal variation in the residual toxicity of the tested formulations could be useful for improving mosquitos’ management programs.

Transgenerational effects of chromium stress at the phenotypic and molecular level in Arabidopsis thaliana - Ilaria Colzi; Cristina Gonnelli; Chiara Vergata; Gabriele Golia; Andrea Coppi; Maria Beatrice Castellani; Antonio Giovino; Matteo Buti; Tommaso Sabato; Maurizio Capuana; Alessio Aprile; Luigi De Bellis; et al. (Journal of Hazardous Materials, 2023)

Hemophagocytic lymphohistiocytosis diagnosed by bone marrow trephine biopsy in living post-COVID-19 patients: case report and mini-review - Maria Ioannou; Konstantina Zacharouli; Sotirios G. Doukas; Michael D. Diamantidis; Vaya Tsangari; Konstantinos Karakousis; George K. Koukoulis; Dimitra P. Vageli (Journal of Molecular Histology, 2022)

Efficacy of polydimethylsiloxane against Culex pipiens (Diptera: Culicidae) - Anastasia J. Nikolaidou; Charalampos S. Ioannou; Nikos T. Papadopoulos; Christos G. Athanassiou (Environmental Science and Pollution Research, 2021)

Donepezil induces ventricular arrhythmias by delayed repolarisation - Jason Kho; Adam Ioannou; Amit K J Mandal; Constantinos G Missouris (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Smad4 and epithelial–mesenchymal transition proteins in colorectal carcinoma: an immunohistochemical study - M. Ioannou; E. Kouvaras; R. Papamichali; M. Samara; I. Chiotoglou; G. Koukoulis (Journal of Molecular Histology, 2018)

Hemodynamic impact of abdominal aortic aneurysm stent-graft implantation-induced stenosis - Nicolas Aristokleous; Nikolaos G. Kontopodis; Konstantinos Tzirakis; Christos V. Ioannou; Yannis Papaharilaou (Medical & Biological Engineering & Computing, 2016)

Aurora B kinase in Hodgkin lymphoma: immunohistochemical pattern of expression in neoplastic Hodgkin and Reed-Sternberg cells - M. Ioannou; E. Kouvaras; E. Stathakis; M. Samara; G. K. Koukoulis (Journal of Molecular Histology, 2014)

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)
The variation of the smaller size fraction of zooplankton was investigated during a two-year period in a brackish deep and anoxic coastal lake of western Greece (Aitoliko), along with the specific environmental characteristics of this ecosystem. The zooplanktonic community comprised a relatively small number of taxa and it was dominated by brackish-water calanoid copepods (Paracartia latisetosa, Calanipeda aquaedulcis) and in certain periods by rotifers and tintinnids. The zooplankton abundance showed an increase in the warmer period starting from late spring and reached maximum values in July. In the well oxygenated surface layer, temperature was the most important parameter influencing the seasonal cycles of all groups. In contrast, the oxygen depletion a few meters under the surface affected the vertical distribution of most of the zooplankton groups, which were found restricted in the surface layer especially from spring until autumn. Only the meroplanktonic larvae of polychaetes presented increased proportions in the deeper layers. Salinity has not significantly influenced the zooplanktonic assemblages. The results point out the degraded status of the Aitoliko basin where the hypoxic/anoxic layers resulted to a high portion of dead organic material identified as copepod carcasses, and underlines the necessity of monitoring of this ecosystem.

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)

Hierarchical radial and polar organisation of chromosomes in human sperm - N. M. Millan; P. Lau; M. Hann; D. Ioannou; D. Hoffman; M. Barrionuevo; W. Maxson; S. Ory; H. G. Tempest (Chromosome Research, 2012)

Twenty-four chromosome FISH in human IVF embryos reveals patterns of post-zygotic chromosome segregation and nuclear organisation - D. Ioannou; K. G. L. Fonseka; E. J. Meershoek; A. R. Thornhill; A. Abogrein; M. Ellis; D. K. Griffin (Chromosome Research, 2012)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: application to the Akrotiri basin and aquifer, Cyprus - A. D. Koussis; E. Georgopoulou; A. Kotronarou; K. Mazi; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; C. Ioannou; A. Georgiou; et al. (Hydrological Sciences Journal, 2010)

First occurrence of Scarus ghobban (Actinopterygii: Scaridae) in the coastal waters of Cyprus (Eastern Mediterranean Sea) - G. IOANNOU; N. MICHAILIDIS; A. LOUCAIDES; I. MANITARAS (Mediterranean Marine Science, 2010)
The first occurrence of the Indo-Pacific blue-barred parrotfish (Scarus ghobban) in the coastal waters of Cyprus is reported. The finding corroborates the establishment of this Lessepsian immigrant along the Levantine coasts.

Inventory of alien marine species of Cyprus (2009) - S. KATSANEVAKIS; K. TSIAMIS; G. IOANNOU; N. MICHAILIDIS; A. ZENETOS (Mediterranean Marine Science, 2009)
An updated inventory of alien marine species from coastal and offshore waters of Cyprus is presented. Records were compiled based on the existing scientific and grey literature, including HCMR database of Mediterranean alien species, technical reports, scientific congresses, academic dissertations, and websites, as well as on unpublished/personal observations. The listed species were classified in one of five categories: established, invasive, casual, cryptogenic, and questionable. The mode of introduction and the year of first sighting were also reported for each species. Eight new records based on personal observations of the authors were reported (Chondria coerulescens, Neosiphonia sphaerocarpa, Enchelycore anatina, Lagocephalus spadiceus, Lagocephalus suezensis, Scomberomorus commerson, Sillago sihama, and Sphoeroides pachygaster). Nine species, previously reported as aliens in Cypriot waters, were excluded from the inventory for various reasons. Ten established species were characterized as invasive (Caulerpa racemosa var. cylindracea, Cerithium scabridum, Strombus persicus, Trochus erythraeus, Brachidontes pharaonis, Pinctada radiata, Fistularia commersonii, Lagocephalus sceleratus, Siganus luridus, and Siganus rivulatus) as they have a substantial impact on biodiversity and/or local economy. The impact of alien marine species in Cyprus is expected to grow in the close future, and further effort directed towards recording alien invasions and their impact will be needed.

Arsonoliposomes for the Potential Treatment of Medulloblastoma - Marco E. Favretto; Showan Marouf; Panagiotis Ioannou; Sophia G. Antimisiaris; Terence L. Parker; Paraskevi Kallinteri (Pharmaceutical Research, 2009)

Quantum dots as new-generation fluorochromes for FISH: an appraisal - Dimitris Ioannou; Helen G. Tempest; Benjamin M. Skinner; Alan R. Thornhill; Michael Ellis; Darren K. Griffin (Chromosome Research, 2009)

Arsonoliposomes, a Novel Class of Arsenic-Containing Liposomes: Effect of Palmitoyl-Arsonolipid-Containing Liposomes on the Viability of Cancer and Normal Cells in Culture - Olga Gortzi; Evangelia Papadimitriou; Christos G. Kontoyannis; Sophia G. Antimisiaris; Panayiotis V. Ioannou (Pharmaceutical Research, 2002)

Multicenter randomized trial of fluconazole versus amphotericin B for treatment of candidemia in non-neutropenic patients - P. Phillips; S. Shafran; G. Garber; C. Rotstein; F. Smaill; I. Fong; I. Salit; M. Miller; K. Williams; J. M. Conly; J. Singer; S. Ioannou (European Journal of Clinical Microbiology & Infectious Diseases, 1997)